Association of Neutrophil-to-lymphocyte Ratio with Prognosis in Sepsis - An Observational Study from a Tertiary Care Center - Birjesh Kumar Thakran; Yogesh Kumar Chahar; Shikha Jain; Sundeep Jain (Wolters Kluwer Medknow Publications, 2023)
Objectives: This study aims to determine the association of neutrophil-lymphocyte ratio (NLR) with sequential organ failure assessment (SOFA) score, ventilator use, duration of intensive care unit (ICU) stay, and mortality among patients with sepsis. Methods: This prospective observational study included 220 patients with sepsis admitted to the ICU. Details such as age, gender, comorbidities, complaints, SOFA score, diagnosis, and outcomes were collected. Routine investigations included complete blood count, C-reactive protein, and procalcitonin. NLR was derived using the Beckman Coulter DXH-800 Hematology Analyser. A cutoff of 9.11 was taken as high NLR. Patients were followed up till 28 days after treatment. The outcomes studied included 28-day mortality and ICU stay. Results: The mean SOFA score were 7.07 ± 2.56. Based on NLR cutoffs, 146 (66.36%) patients had high NLR while 74 (33.64%) cases had normal or low NLR. SOFA score showed no significant association with high NLR (P = 0.62). Ventilator was used in 118 (53.6%) cases with median of 3.5 days' duration. The overall ICU stay was 5.6 ± 4.9 days. Mortality was seen in 46 (20.9%) cases. Compared to those with normal NLR, patients with high NLR had significantly more ventilator use (60.9% vs. 39.1%, P = 0.0027) and mortality (30.14% vs. 2.7%, P = 0.0004). The duration of ventilator use and ICU stay was statistically comparable. Conclusion: High NLR shows a significant association with adverse outcomes of sepsis patients in terms of ventilator use and mortality. Since it is cheap and easy to use, it can be applied in more basic settings while monitoring sepsis patients.